Evaluating Electron Paramagnetic Resonance (EPR) to Measure Lipid Oxidation Lag Phase for Shelf‐Life Determination of Oils. (30th November 2016) - Cui, Leqi; Lahti, Paul M.; Decker, Eric A.
Abstract: Lipid oxidation is one of the major causes of oil deterioration causing off‐flavors and consumer rejection. Fast, easy, and dependable assays for predicting lipid oxidation rates in foods are important for shelf‐life prediction. In this study, an electron paramagnetic resonance (EPR) spin‐trapping technique with N ‐ tert ‐butyl‐α‐phenylnitrone (PBN) was tested to determine the lag phase of lipid oxidation in stripped soybean oil (SSO), SSO with added α‐tocopherol, and commercial soybean, canola and corn oils. EPR intensity of spin‐trapped products from SSO correlated well with lipid hydroperoxides formation for samples stored at 37 and 55 °C respectively. When the antioxidant α‐tocopherol was added, the EPR signal intensity of oil samples increased—indicating sample deterioration—after 50–65% of α‐tocopherol was consumed. When using the EPR method with commercial soybean, canola or corn oil stored at 55 °C, there was a poor relationship between EPR intensity and lipid hydroperoxides lag phases. However, a linear correlation was found between EPR signal intensity and hexanal formation. For example, EPR signal intensity lag phases were 5, 13 and 27 days for soybean, canola and corn oils, respectively which was similar to the hexanal lag phases of 5, 13 and 25 days for the same oils. The EPR spin‐trapping assay method has several advantages over headspace hexanal measurements, especially with regard to easier sample handling and shorter analysis times.